2021
DOI: 10.15694/mep.2021.000136.1
|View full text |Cite
|
Sign up to set email alerts
|

Blogging for the Continuum of Medical Education: Engaging Diverse Communities of Learners

Abstract: In response to the COVID-19 pandemic, colleges and universities established remote teaching and reestablished best practice-based, active education using discussion boards and other means to promote learner collaboration. Increasingly, social media or open educational technology platforms contribute to blended learning. This short article aims to introduce blogs for delivering barrier-free online education to targeted public audiences and groups of learners. Blogs disseminate ideas within a tangible, searchabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The blog has been a panacea for isolation and idleness during Covid-19. Radjuni (2022;Schlegel & Primacio, 2021) initiates a study that seeks to promote learners' independence in a 4.0 learning environment during the COVID-19 pandemic and create an engaging diverse community of learners in medical education. The authors aim to improve student writing skills through blogging, and it was found in the study that the students are interested in the continual use of blogs even after the academic session (Forrester, Ashman & Kuebbing, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The blog has been a panacea for isolation and idleness during Covid-19. Radjuni (2022;Schlegel & Primacio, 2021) initiates a study that seeks to promote learners' independence in a 4.0 learning environment during the COVID-19 pandemic and create an engaging diverse community of learners in medical education. The authors aim to improve student writing skills through blogging, and it was found in the study that the students are interested in the continual use of blogs even after the academic session (Forrester, Ashman & Kuebbing, 2022).…”
Section: Introductionmentioning
confidence: 99%